Health-related quality of life in Iranian adult men with severe hemophilia. Issue 8 (December 2017) - Faranoush, Mohammad; Shahverdi, Ehsan; Ghorbani, Raheb; Moghaddam, Mostafa
Abstract : N/A: Health-related quality of life (HRQOL) assessment should be part of the regular clinical assessment of persons with hemophilia. This study assessed quality of life of severe hemophilia patients (Type A) in Tehran comprehensive hemophilia care center. This cross-sectional study was done in 2016 and 84 men aged over 20 years with severe hemophilia (Type A) were assessed. All patients have been treated over 10 years at the comprehensive hemophilia care center, Iran. The HRQOL assessment includes the A36 Hemophilia-QOL questionnaire, sociodemographical and clinical characteristics. The overall HRQOL mean (±SD) in the present sample was 69.1 ± 26.0 (A36Hemofilia-QoL Global Index). The mean (±SD) scores according the domains were: physical health (15.0 ± 5.7), daily activities (6.7 ± 3.8), joint damage (4.2 ± 2.9), pain (3.0 ± 1.9), social activities and relationships (10.7 ± 5.8) and emotional function (9.2 ± 5.0) classified moderate-to-poor state. In contrast with treatment satisfaction (4.8 ± 1.6), treatment difficulties (9.5 ± 3.4) and mental health (6.2 ± 3.3), those were all in moderate-to-good state. Patients with higher education levels had better quality of life in the area of anxiety ( P = 0.034), mental health ( P = 0.007), social activities and personal relationships ( P = 0.002). In general, poor quality of life of patients was 13.1%, 42.9% weak-to-moderate, 38.1% moderate-to-good and 6% good. It was shown that over 50% of patients had low-to-moderate HRQOL in the domains, such as physical health, daily activities, joint damage, pain, social activities and personal relationships. Efforts are necessary to improve their HRQOL.